Dynamic fairness evaluation framework for cloud computing - Di LU; Jian-feng MA; Yi-chuan WANG; ing XIN; Xian-jia MENG (Tongxin xuebao)
Dynamic fairness evaluation framework (DFE) was given according to the dynamic features of resources in cloud environment. In DFE, the factors of fairness, efficiency and time were introduced, and the allocation results were processed into numeric values, which could measure the fairness of allocation algorithms quantificationally. Two typical dynamic factors in cloud environment are considered, dynamic resource demands of virtual nodes and dynamic quantity of virtual node number. Then, two sub-models are established for both of the dynamic factors, with which DFE is finally derived. Both of the sub-models and DFE are analyzed, and evaluated with several typical resource allocation algorithms. The experimental results prove that DFE can effectively provide a measurement for allocation fairness evaluation in the case of both dynamic resource demands and node number.